Occupational contact dermatitis in blue‐collar workers: results from a multicentre study from the Danish Contact Dermatitis Group (2003–2012). (18th July 2014) - Schwensen, Jakob F.; Menné, Torkil; Veien, Niels K.; Funding, Anne T.; Avnstorp, Christian; Østerballe, Morten; Andersen, Klaus E.; Paulsen, Evy; Mørtz, Charlotte G.; Sommerlund, Mette; Danielsen, Anne; Andersen, Bo L.; et al.
Summary Background Blue‐collar workers have a high risk of occupational contact dermatitis, but epidemiological studies are scarce. Objectives To investigate allergic contact dermatitis in blue‐collar workers with dermatitis registered by the Danish Contact Dermatitis Group. Methods A retrospective analysis of patch test data from 1471 blue‐collar workers and 1471 matched controls tested between 2003 and 2012 was performed. A logistic regression was used to test for associations. Results The blue‐collar workers often had occupational hand dermatitis (p < 0.001). Atopic dermatitis was less commonly observed among blue‐collar workers (19.6%) than among controls (23.9%) (p = 0.005). Allergens with a statistically significant association with the occupational group of blue‐collar workers were epoxy resins, methyldibromo glutaronitrile, 2‐bromo‐2‐nitro‐1, 3‐propanediol, potassium dichromate, and methylchloroisothiazolinone (MCI)/methylisothiazolinone (MI). The following occupations were additionally identified as risk factors for contact sensitization to MCI/MI and MI, epoxy resins, and potassium dichromate, respectively: painting, construction work, and tile setting/terrazzo work. Conclusion Contact allergy is a major problem among blue‐collar workers. The data indicate a healthy worker effect among blue‐collar workers diagnosed with dermatitis, as blue‐collar workers were diagnosed significantly less often with atopic dermatitis than were controls.